2015
DOI: 10.1371/journal.pone.0131834
|View full text |Cite
|
Sign up to set email alerts
|

Injuries, Death, and Disability Associated with 11 Years of Conflict in Baghdad, Iraq: A Randomized Household Cluster Survey

Abstract: BackgroundThe objective of this study was to characterize injuries, deaths, and disabilities arising during 11 years of conflict in Baghdad.MethodsUsing satellite imagery and administrative population estimated size for Baghdad, 30 clusters were selected, proportionate to population size estimates. Interviews were conducted during April and May 2014 in 900 households containing 5148 persons. Details about injuries and disabilities occurring from 2003 through May 2014 and resultant disabilities were recorded.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 29 publications
8
42
1
Order By: Relevance
“…The vast majority of injuries were due to blast or explosion, consistent with findings of the effect of conflict on injury patterns in Baghdad from 2003 [30]. …”
Section: Discussionsupporting
confidence: 80%
“…The vast majority of injuries were due to blast or explosion, consistent with findings of the effect of conflict on injury patterns in Baghdad from 2003 [30]. …”
Section: Discussionsupporting
confidence: 80%
“…While we are unable to infer the epidemiology of injury in the population from these hospital-based data, the findings support other studies from Iraq that suggest unintentional injuries predominate in populations affected by prolonged insecurity. [19][20][21] A population-based survey of injuries in Baghdad from 2003-2014 reported that falls, road traffic crashes, and mechanical injuries were more common than all violence-related injuries combined. 20 The authors concluded that deterioration of infrastructure, changes in safe behavior, and a lack of injury prevention and control programs contribute to this epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…They measure mortality by asking respondents to report deaths among their relatives. Questions asking whether the deaths of these relatives are due to injuries, accidents, or conflicts have been asked in several surveys, such as DHS in Zimbabwe and Zambia, the WHO's World Health Survey (Obermeyer, Murray, and Gakidou 2008), and postconflict surveys (Hagopian et al 2013;Lafta et al 2015). A few studies have compared estimates of conflict-related deaths derived from such surveys to estimates from other sources (Obermeyer, Murray, and Gakidou 2008).…”
Section: Introductionmentioning
confidence: 99%